Manajemen Strategi Pemerintah Desa dalam Pelaksanaan Program Ketahanan Pangan - Alfriani, Jesica; Rifai, Maulana; Aryani, Lina (Journal of Government Insight, 2024)
This research aims to determine the strategic management of the Sukaluyu Village Government in the Food Security Program. It is important to know this strategic management pattern to become a reference for the implementation of similar programs, so that we can also see the mitigation patterns carried out in dealing with obstacles in its implementation, especially in the implementation of the Sukaluyu Village Food Security Program. The research was conducted using qualitative research methods through a descriptive approach. Qualitative research seeks to interpret a person's point of view in seeing and describing their social world. Meanwhile, descriptive research is research that can describe a phenomenon by including facts that are explained in more detail. This method is appropriate for this research. Research findings based on strategic management by Wheelen & Hunger in the Sukaluyu Village Food Security Program include 1) environmental observations; carried out by observing aspects of land availability, diversity of food types, readiness and consistency of implementers, 2) strategy formulation; carried out with coordination between the government and implementers, 3) strategy implementation; carried out by the stated goals and missions, and 4) evaluation and control. The benefit of this research is as a reference or point of reference for future research.